Factors Affecting Return on Asset at Himbara Bank in Indonesia - Nanda Destiliansi; Eka Dewi Anggraini (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This research aims to analyze the influence of Net Interest Margin (NIM), Operating Expenses, Operating Income (BOPO), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR) on Return On Assets at State-Owned Association Banks (HIMBARA) in Indonesia. This type of research uses secondary data based on 2010-2022 panel data. Data were analyzed using panel data regression using the Eviews analysis tool. The research results show that Net Interest Margin (NIM) has a significant effect on Return On Assets (ROA). Operational Income (BOPO) has a significant effect on Return On Assets. Loan to Deposit Ratio (LDR) has no effect on Return On Assets. Meanwhile, Non-Performing Loans (NPL) do not have a significant effect on Return On Assets at Bank Himbara in Indonesia.